PRESEPSI SISWA KELAS XII SMAN 1 RUMBIO JAYA TERHADAP LKPD BERBASIS ANDROID MATA PELAJARAN SEJARAH - Asyrul Fikri; Sina Anisah (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2023)
Most students of Rumbio Jaya 1 public high school consider history lessons to be a boring subject because the methods used by teachers are still using compulsory books. (Student worksheet) android-based history. The research method used in this research is to design learning resources in the form of student worksheets based on android and to carry out the feasibility of LKPD on the learning of students of Rumbio Jaya 1 public high school. Based on the research that has been done, the LKPD learning method (student worksheet) is declared feasible to be used in the teaching and learning process after an analysis by material experts, questions, media, and students. The results of the validation of android-based worksheets on history subjects by material experts get an average score of 4.2 in the appropriate category, question experts with an average score of 4.0 in the appropriate category, media experts with an average score of 4.5 in the appropriate category. very feasible, and assessment by students with an overall average score of 4.3 with a very feasible category. In this study, there are still research limitations, where the research produced is still at the beginner level, so the researchers hope that there will be research that can develop this LKPD learning method so that it can be applied to other schools.